Protective effects of sodium tanshinone IIA sulfonate on cardiac function after myocardial infarction in mice - Wu, Peng (Am J Transl Res, 2019)
Sodium tanshinone IIA sulfonate (STS), a water-soluble derivative of tanshinone IIA, has been used in traditional Chinese medicine for many years. Many experiments have demonstrated that STS has anti-inflammatory, anti-apoptosis and angiogenesis effects. However, it is unclear whether STS has the same beneficial effects on myocardial infarction in vivo. The aim of our experiments was to investigate whether STS could improve cardiac function and prevent myocardial remodeling after myocardial infarction (MI) in mice. The MI model was established by surgical ligation of the left anterior descending (LAD) coronary artery. Then the mice were randomly divided into STS and untreated groups. The results of treatment for 3 weeks showed that STS could increase the survival rate, reduce the release of some inflammatory cytokines, inhibit cell apoptosis and promote angiogenesis. The study presents a new potential treatment method for ischemic heart disease.